Functional characterization of the phosphotransferase system in Parageobacillus thermoglucosidasius - Gonzalo N. Bidart; Hani Gharabli; Ditte Hededam Welner (Scientific Reports, 2023)
Abstract Parageobacillus thermoglucosidasius is a thermophilic bacterium characterized by rapid growth, low nutrient requirements, and amenability to genetic manipulation. These characteristics along with its ability to ferment a broad range of carbohydrates make P. thermoglucosidasius a potential workhorse in whole-cell biocatalysis. The phosphoenolpyruvate:carbohydrate phosphotransferase system (PTS) catalyzes the transport and phosphorylation of carbohydrates and sugar derivatives in bacteria, making it important for their physiological characterization. In this study, the role of PTS elements on the catabolism of PTS and non-PTS substrates was investigated for P. thermoglucosidasius DSM 2542. Knockout of the common enzyme I, part of all PTSs, showed that arbutin, cellobiose, fructose, glucose, glycerol, mannitol, mannose, N-acetylglucosamine, N-acetylmuramic acid, sorbitol, salicin, sucrose, and trehalose were PTS-dependent on translocation and coupled to phosphorylation. The role of each putative PTS was investigated and six PTS-deletion variants could not grow on arbutin, mannitol, N-acetylglucosamine, sorbitol, and trehalose as the main carbon source, or showed diminished growth on N-acetylmuramic acid. We concluded that PTS is a pivotal factor in the sugar metabolism of P. thermoglucosidasius and established six PTS variants important for the translocation of specific carbohydrates. This study lays the groundwork for engineering efforts with P. thermoglucosidasius towards efficient utilization of diverse carbon substrates for whole-cell biocatalysis.